1994
DOI: 10.1111/j.1751-1097.1994.tb05048.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTODYNAMIC THERAPY OF B16 PIGMENTED MELANOMA WITH LIPOSOME‐DELIVERED Si(IV)‐NAPHTHALOCYANINE

Abstract: The possibility of extending photodynamic therapy to the treatment of highly pigmented neoplastic lesions was tested by using Si(IV)-naphthalocyanine (SiNc) as a tumor-localizing agent. Si(IV)-naphthalocyanine displays intense absorbance at 776 nm (epsilon = 5 x 10(5) M-1 cm-1), where melanin absorption becomes weaker. As an experimental model we selected B16 pigmented melanoma subcutaneously transplanted to C57BL mice. Upon injection of 0.5 or 1 mg kg-1 of liposome-incorporated SiNc, maximal accumulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 9 publications
0
31
0
1
Order By: Relevance
“…Our findings suggest that a limited selectivity of melanoma targeting by BPD-MA occurs only at 1-3 h with a concentration ratio of 1.6. In contrast, no selectivity of accumulation in the melanotic melanoma was observed for SiNc (Biolo et al, 1994;Biolo et al, 1996). Both BPD-MA and SiNc were found to give a good selectivity of tumour targeting in other transplanted tumours (Cuomo et al, 1990;Richter et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that a limited selectivity of melanoma targeting by BPD-MA occurs only at 1-3 h with a concentration ratio of 1.6. In contrast, no selectivity of accumulation in the melanotic melanoma was observed for SiNc (Biolo et al, 1994;Biolo et al, 1996). Both BPD-MA and SiNc were found to give a good selectivity of tumour targeting in other transplanted tumours (Cuomo et al, 1990;Richter et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…In this connection, BPD-MA is superior to SiNc, whose clearance from the organism is still incomplete 1 week after i.v. injection (Biolo et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…(C) Lutetium texaphyrin from (Woodburn, Fan et al 1998). (D) Si(IV)-naphthalocyanine (Isobosinc) from (Biolo, Jori et al 1994). Showing red fluorescence from BC 1, 2 or 3 overlaid with green fluorescence from lysotracker, mitotracker or FITC-anti-TRP1 antibody that stains melanosomes.…”
Section: Resultsmentioning
confidence: 99%
“…PDT of the heavily pigmented metastatic B16F10 melanoma using a diamagnetic water-soluble lutetium texaphyrin (PCI-0123) resulted in tumor apoptosis with a significant tumor regrowth decay and increase of survival (Woodburn, Fan et al 1998). Biolo et al (Biolo, Jori et al 1994) used a liposomal formulation of Si(IV)-naphthalocyanine for induction of tumor necrosis and delay of tumor regrowth in B16 pigmented melanoma, although no tumor selectivity was observed.…”
Section: Near Infrared Absorbing Psmentioning
confidence: 99%
“…The beam was piloted to the irradiation site by a bundle of optical fibres whose tip (diameter 0.8 cm) was kept at a distance of 1 cm from the mouse skin. Previous studies (Soncin et al, 1995b) have shown that under these irradiation conditions the tumour temperature does not rise beyond 38°C, so that any hyperthermal effect could be discounted (Biolo et al, 1994). During irradiation the mice were anaesthetised by intraperitoneal administration of ketalar (0.5 ml per 20 g of body weight).…”
Section: Chemicalsmentioning
confidence: 99%